Development and Psychometric Testing of the Academic Clinical Nurse Educator Skill Acquisition Tool. Issue 4 (5th July 2022) - Shellenbarger, Teresa; Sebach, Aaron M.
Abstract: AIM: This article reports the development and psychometric testing of an instrument to measure academic clinical nurse educator skill acquisition. BACKGROUND: Little research explores clinical nurse educator competence. METHOD: Using the National League for Nursing Academic Clinical Nurse Educator core competencies and a literature review, newly created clinical nurse educator skill acquisition items underwent two rounds of content validity testing. The resulting 40-item Academic Clinical Nurse Educator Skill Acquisition Tool was pilot tested with a convenience sample of 133 clinical nurse educators. RESULTS: The Academic Clinical Nurse Educator Skill Acquisition Tool demonstrated adequate validity and internal consistency reliability. Factor analysis identified two factors: facilitating clinical learning through the use of effective teaching, assessment, and evaluation and promoting nursing enculturation. CONCLUSION: Further use of this tool may provide insight about the psychometrics, offer information about clinical teaching competence, and could lead to improved orientation and mentoring programs for clinical nurse educators.